Política y religión : teología pública para un mundo plural - Yaksic, Miguel, S.J (Teología de los tiempos, 2011)
Moral, aesthetic, and religious pluralism has become a source of disagreement and friction in the modern world. Within the context of modernity and precipitated by the American and French revolutions, liberal democracy has aimed to organize the social and political life of societies in which their inhabitants sustain different, distant, and sometimes contradictory conceptions of the good life. Liberal secular principles have been the framework used to protect fundamental values such us freedom, equality, and mutual respect. In order to preserve the stability of a plural society, liberalism insists that moral and religious convictions must remain a private matter. Democracy and tolerance, it was argued, would be best preserved if religious convictions were removed from the public/political conversation. Yet the debate about the appropriate relationship between religion and politics regularly resurfaces among political and moral philosophers, social theorists, and theologians.